Paywall vs. Clickbait: Comparative Analysis of the Digital Media Discourse on Two Opposing Strategies - Monsalve-Alamá, Antonio; Ortigosa-Blanch, Arturo; Marti-Sanchez, Myriam (Transformations In Business & Economics, 2024)
Media companies have sought new ways of marketing their content for several years. In the search for financial stability, the media has tested several models, two of which stand out: paywalls and clickbait. The study examined and compared the Spanish media discourse when publishing content related to these two opposing models. Two linguistic corpora were used. These corpora were built from journalistic content spanning a period of 15 years. A total of 4,410 articles were retrieved. Semantic and thematic analysis techniques were used to analyse the data, and an unsupervised clustering process was applied. Notable conclusions include the finding that the media discourse links the paywall model with higher quality and loyalty, whereas the clickbait model is linked to sensationalism and falsified content. These findings coincide with the connotations that experts attribute to each model.
Keywords: digital business models; paywall; clickbait; media; semantic analysis; Spain